Impact of Integrated Vs. Traditional Curriculum Models on Long-Term Clinical Skills Retention: Integrated Vs. Traditional Curriculum Models - Jalal, Sammer Fatima; Ayub, Hassan; Parveez, Farida; Amin, Sarah; Khan, Fatima Muhammad; Afridi, Sanodia (Pakistan Journal of Health Sciences, 2025)
Integrating basic and clinical sciences has been promoted to enhance clinical reasoning and long-term retention in medical education. Objectives: To compare six-month retention of knowledge and interpretation-based clinical reasoning skills among undergraduate medical students taught through integrated versus traditional curriculum models. Methods: A quasi-experimental study was conducted among final-year medical students (Integrated curriculum: n=53; Traditional curriculum: n=48). Baseline and six-month follow-up assessments included multiple-choice questions (MCQs) for knowledge and interpretation tasks for clinical reasoning. Objective Structured Clinical Examination (OSCE) scores were also recorded. Independent samples t-tests were applied for normally distributed data and Mann–Whitney U tests for non-normal data, based on Shapiro–Wilk normality results. Effect sizes and 95% confidence intervals (CIs) were calculated. A p-value <0.05 was considered statistically significant. Results: Baseline MCQ and interpretation scores were comparable between groups. At six months, knowledge retention (MCQ scores) declined in both groups without a significant between-group difference (p=0.074). Interpretation scores were higher in the integrated group (mean difference 0.48, 95% CI 0.11–0.85, p=0.012), representing a small but statistically significant advantage. OSCE performance was slightly better in the integrated group but did not reach statistical significance (p=0.083). Conclusions: The integrated curriculum was associated with a small but statistically significant advantage in preserving interpretation-based clinical reasoning over six months, despite similar knowledge and procedural skill retention. While the effect size is modest, these findings support the relevance of curriculum integration for fostering higher-order reasoning, particularly when coupled with reinforcement strategies.